2019
DOI: 10.15611/pn.2019.7.03
|View full text |Cite
|
Sign up to set email alerts
|

Expenditure on research and development activities as a determinant of the innovativeness of the European Union’s economy

Abstract: This article aims to determine to what extent and with what time delay expenditure on research and development activity are determined by the effects of innovative activity. The accepted research hypothesis is that the positive impact of expenditure on research and development activity on its results is visible already after one or two years from when they were incurred. In order to empirically verify the proposed research hypothesis, the correlation between selected variables relating to R&D spending in 2013-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…The literature review, as well as the authors' own empirical analyses, indicate that one of the main determinants of innovativeness (both before and during the pandemic) are expenditures of the business sector on R&D (e.g. Huňady & Pisár, 2021;Firlej, 2019) as well as education expressed through participation in lifelong learning and the percentage of people with tertiary education (e.g. Denkowska et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The literature review, as well as the authors' own empirical analyses, indicate that one of the main determinants of innovativeness (both before and during the pandemic) are expenditures of the business sector on R&D (e.g. Huňady & Pisár, 2021;Firlej, 2019) as well as education expressed through participation in lifelong learning and the percentage of people with tertiary education (e.g. Denkowska et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Among the keywords in an area related to regression analysis, however it is very small. Studies have been reported in the literature on measuring innovation [ 34 – 36 ], the dimensions of measuring innovation and R&D performance [ 37 , 38 ], to select various indicators and methods for its assessment [ 8 ]; the literature review in term of innovativeness measures were classified in terms of inputs, capabilities and outputs [ 39 ], impact of expenditure on research and development activity on its results [ 40 ], the relationship between innovation investment and regional innovation performance [ 41 ], the use of innovation scoreboards as a main device for policy monitoring and benchmarking [ 42 ], a procedure of measurement of innovativeness growth over time [ 43 ], taxonomic methods of measure development in this innovation area [ 44 ] and formal model for measuring R&D performance [ 45 ]. On this basis, the variables presented in the research methodology were selected.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The inherent elements of innovative activity, on the basis of which it can be assessed, are, on the one hand, input components, which include, among others, outlays (expenses) on innovation, including R&D activity. On the other hand, there are exit elements that are extremely diverse, and their selection in many cases depends on the purpose and context of the entire research (Bilbao-Osorio & Rodriguez-Pose, 2004 ; Carlson, 2011 ; Firlej, 2019 ). The effects of innovative activity may include aspects related to the improvement of product quality, but also, apart from strictly product changes, streamlining work, and improving production efficiency (Babuchowska & Marks-Bielska, 2021 ).…”
Section: Literature Reviewmentioning
confidence: 99%